PENGGUNAAN PEN TABLET DENGAN APLIKASI GOOGLE MEET UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SMK - NURAINI NURAINI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2021)
This Best Practice is implemented to improve mathematics learning outcomes of vocational through the use of a Pen Tablet with the Google Meet application. The subjects of this study were 155 students of SMKN 5 Kota Serang class XII OTKP and XII TKJ who were conducted in the odd semester of the 2021/2022 academic year with the material: Three Dimensional Geometry, Statistics and Probability. This Best Practice describes the learning process using media in the form of a Pen Tablet with the Google Meet application. Quantitative data were obtained from daily test scores with written test techniques in the form of descriptions, while qualitative data were obtained from observations of student activity. After students were taught mathematics using Pen Tablet with the Google Meet application, learning outcomes increased by 24.6% from the average chapter 1 material of 62,00 which continued to increase in chapter 3 material to 77.25. The implementation of Best Practice shows that the use of the Pen Tablet with the Google Meet application can improve the mathematics learning outcomes of SMK students, especially students of class XII OTKP and XII TKJ SMKN 5 Kota Serang in the odd semester of the 2021/2022 academic year. ABSTRAKBest Practice ini dilaksanakan untuk meningkatkan hasil belajar matematika SMK melalui penggunaan Pen Tablet dengan aplikasi Google Meet. Subyek dari penelitian ini adalah siswa SMKN 5 Kota Serang kelas XII OTKP dan XII TKJ yang berjumlah 155 orang yang dilakukan pada semester ganjil tahun ajaran 2021/2022 dengan materi : Geometri Dimensi Tiga, Statistika dan Peluang. Best Practice ini menggambarkan tentang proses pembelajaran menggunakan media berupa Pen Tablet dengan aplikasi Google Meet. Data kuantitatif diperoleh dari nilai ulangan harian dengan teknik test tertulis bentuk uraian, sedangkan data kualitatif diperoleh dari hasil observasi keaktifan siswa. Setelah siswa diajarkan matematika menggunakan Pen Tablet dengan aplikasi Google Meet hasil belajar meningkat sebesar 24,6 % dari rata-rata materi bab 1 62,00 meningkat terus pada materi bab 3 menjadi 77,25. Pelaksanaan Best Practice menunjukkan bahwa penggunaan Pen Tablet dengan aplikasi Google Meet dapat meningkatkan hasil belajar matematika siswa SMK terutama siswa kelas XII OTKP dan XII TKJ SMKN 5 Kota Serang semester ganjil tahun ajaran 2021/2022.